An unusual Lecythophora fungal keratitis case report: - - Qonita Imma Irfani; R Ludhang Pradipta Rizki; Suhardjo (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2022)
Introduction: The infective process of the cornea caused by any number of pathological fungi that can invade the ocular surface is referred to as fungal keratitis or Keratomycosis. Fungal keratitis is a major vision-impairing condition worldwide as it is so difficult to treat. In order to prevent or reduce severe complications following an infection, microbiological culture and direct microscopic examination are critical to be done. Thus, early diagnosis and prompt treatment can be established. In this report, we want to explain a rare case of Lecythophora spp. fungal keratitis on women with ocular trauma caused by the rope’s end.Case Description: A 62-year-old woman presented to the hospital with complaints of watery eyes, redness, corneal ulcer, and a sensation of something in the eye in her left eye for 12 days with progressive vision loss. A history of left eye trauma was found. The patient had left ocular trauma from the rope end. There were no other symptoms that suggested an underlying disease. On microbial examination, we observed a Lecythophora spp. The colony was flat, smooth, moist to slimy, pink to violet on the surface, and tan on the reverse. Antifungal susceptibility tests revealed the species was still tolerant to Terbinafine, while resistance to Ketoconazole, Fluconazole, and Itraconazole was detected. Because Terbinafine was unavailable, the patient was still receiving ketoconazole, fluconazole, and natamycin therapy. Therefore no significant improvement was achieved. The patient continued to require corneal ulcer debridement twice a day to gain further improvement.Conclusion: Fungal Keratitis or Keratomycos is an invasive infection caused by a variety of Fungi, and sometimes it can be happened by the history of Corneal trauma and make a progressive decrease in vision.